The impact of geographical context on willingness to pay for mobile data and change incentives to disclose personal information - Vale, Miguel Alves do (2020)
Increasing consumer mobility and significative dependence on mobile internet exposes users to constant trade-off decisions between browsing websites and disclosing sensitive information. There is extensive literature on consumer behaviour towards information disclosing and some literature on willingness to pay for mobile services, but there is insufficient research on how the geographical context impacts these behaviours. Based on experimental data gathered through a survey, this dissertation explores the effect of geographical context on the willingness to pay for mobile internet and change the incentives to disclose personal information. In addition, a theoretical relationship between these two variables is discussed. Moderating factors such as data allowance and privacy banner attributes are considered, and linear mixed effects models are employed. This study finds that when abroad, given the same data allowance as when home, the willingness to pay for mobile data increases by 42.0% (p<0.01) and consumers are slightly more willing to disclose personal information. This effect naturally decreases with lower data allowance provided abroad. Furthermore, we find evidence of higher willingness to pay for mobile data in consumers who are more willing to disclose personal information. Subset analysis suggests significant robustness of the findings for willingness to pay but limited robustness for other findings. This dissertation contributes to literature by isolating the impact of the geographical context on willingness to pay for mobile data and disclose personal information, while providing relevant insights for managerial decision making in the telecommunications sector.